Determination of Yield and Yield Components in Some Local Confectionary Sunflower (Helianthus annuus L.) Populations - Levent YAZİCİ (ISPEC Journal of Agricultural Sciences, 2020)
The aim of this study to determinate the yield and yield components of local confectionary sunflower population collected from different regions of Turkey. The research was carried out in Tokat-Kazova ecological conditions according to the rectangular lattice test design with 3 repetitions for 2 years. Plant height, head diameter, grain width, grain height, 1000 grain weight and seed yield were investigated in the study. In the research, material collected from different regions of our country, twenty pieces of local confectionary sunflower population and two registered types were used as standard. According to the average results of two years; plant height values varied between 154.3-265.4 cm, table diameter 17.0-22.2 cm, grain width 7.9-9.6 mm, grain size 20.4-25.9 mm, 1000 grain weight 122.2-167.1 g and seed yield between 180.4-474.0 kg / da. When the characteristics examined in the study are evaluated together, it has been observed that the populations numbered 16, 3, 10, 13 and 14 stand out.